1995
DOI: 10.1177/000348949510401003
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Surgical Treatment of Cancer of the Larynx

Abstract: The purpose of the study was to assess the quality of life of patients after surgical treatment for cancer of the larynx. Three groups of patients were identified according to surgical treatment: total laryngectomy, 111 patients; near-total laryngectomy, 38 patients; and partial laryngectomy, 23 patients. The impact of successful surgical treatment on their life roles was analyzed in terms of work, activities, familial and spousal relationships, sexuality, and psychologic features such as stress and anxiety. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
93
0
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 14 publications
5
93
0
7
Order By: Relevance
“…1,5,6 The need for a standardized quality of life assessment tool is necessary in order to compare results between different institutions and studies. 7,8 Because multidimensionality and OtolaryngologyHead and Neck Surgery Volume 129 Number 1 FERRER et al 95 subjectivity are the 2 main characteristics of quality of life, measurement tools should cover a broad range of content, including physical, emotional, and social well-being. In our study, a permanent stoma and loss of speech are not the critical factors that determine patients' quality of life after surgery for laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,6 The need for a standardized quality of life assessment tool is necessary in order to compare results between different institutions and studies. 7,8 Because multidimensionality and OtolaryngologyHead and Neck Surgery Volume 129 Number 1 FERRER et al 95 subjectivity are the 2 main characteristics of quality of life, measurement tools should cover a broad range of content, including physical, emotional, and social well-being. In our study, a permanent stoma and loss of speech are not the critical factors that determine patients' quality of life after surgery for laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the guidelines reported in the literature. 8 Only 15% of patients undergoing radical surgery and 50% of those undergoing a supraglottic laryngectomy went back to work after surgery. Among the patients who underwent partial vertical surgery, 85.7% went back to work.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in many studies performed, speech has been emphasized as the most influential factor affecting quality of life. [13,15,18,22,23] An unfavorable trend was seen in many quality of life variables of the patients during the first months after chemoradiotherapy, while at subsequent months, especially after 2nd month, improvements in these variables were observed. Graeff et al [24] observed marked improvement in the post-treatment quality of life of laryngeal cancer patients followed up for one year after radiotherapy, but they could not detect marked improvement in complaints of thick saliva, sensory problems and dry mouth at 12th month.…”
Section: Discussionmentioning
confidence: 98%
“…Além do mais, estudos demonstraram que um dos fatores de maior impacto na sobrevida era a manutenção da traqueostomia 10 .…”
Section: Discussionunclassified